Remarkable Diversity of Escherichia coli Carrying mcr-1 from Hospital Sewage with the Identification of Two New mcr-1 Variants - Zhao, Feifei; Feng, Yu; Lü, Xiaoju; McNally, Alan; Zong, Zhiyong (Frontiers in Microbiology, 2017)
The plasmid-borne colistin-resistant gene mcr-1 has rapidly become a worldwide public health concern. This study aims to determine the host bacterial strains, plasmids and genetic contexts of mcr-1 in hospital sewage. A 1-ml hospital sewage sample was cultured. Colistin-resistant bacterial colonies were selected on agar plates and were subjected to whole genome sequencing and subsequent analysis. The transfer of mcr-1 between bacterial strains was tested using conjugation. New variants of mcr-1 were cloned to test the impact of variations on the function of MCR-1. Plasmids carrying mcr-1 were retrieved from GenBank for comparison based on concatenated backbone genes. In the sewage sample, we observed that mcr-1 was located in various genetic contexts on the chromosome, or plasmids of four different replicon types (IncHI2, IncI2, IncP and IncX4), in Klebsiella pneumoniae, Kluyvera spp. and seven Escherichia coli strains of different sequence types (ST10, ST34, ST48, ST1196, ST7086 and ST7087). We also identified two new variants of mcr-1, mcr-1.4 and mcr-1.7, both of which encode an amino acid variation from MCR-1. mcr-1-carrying IncX4 plasmids, which have a global distribution across the Enterobacteriaceae, is the result of global dissemination of a single common plasmid, while IncI2 mcr-1 plasmids appear to acquire mcr-1 in multiple events. In conclusion, the unprecedented remarkable diversity of species, strains, plasmids and genetic contexts carrying mcr-1 present in a single sewage sample from a single healthcare site highlights the continued evolution and dynamic transmission of mcr-1 in healthcare-associated environments.